Playing the Waves Lars von Trier's Game Cinema - Simons, Jan (Film Culture in Transition, 2007)
Dogma95 has been heralded as the European alternative to the Hollywood Blockbuster. For many critics and film lovers, Dogma95 and Von Trier's films have become synonymous with the notions usually associated with independent film making: low budgets and realism. Von Trier's approach to film making, however, takes cinema beyond the traditional confines of film aesthetics and radically transposes the practice of film making and film itself right into what has become the paramount genre of new media: games and gaming. Dogma 95, this book argues, is not an exceptional phase in Von Trier's carreer - as it was for his cofounders - but the most explicit formulation of Von Trier's cinematic games aesthetics, that has guided the conception and production of all of his films. The launching of Dogma95 and the infamous Dogma Manifesto was a game; Von Trier redefines the practice of film making as a rule bound activity, he brings forms and structures of games to bear on his films, and he draws some sobering lessons from economic and evolutionary game theory. Von Trier's films can be better understood from the perspective of games studies and game theory than from the point of view of traditional film theory and film aesthetics.